Islamic Finance: Is it a Time to be Considered as an Alternative during Financial Crisis Times? A Comparative Study in Gulf Cooperation Council - Salim, Badreldin F.; Mahmoud, Mohamed H. (International Journal of Economics and Financial Issues, 2016)
This paper investigates the difficulties facing Islamic finance performance during the financial crisis times and to what extent whether the time has now come to considered it as suitable alternative in such situations as there is general believe that it is the time now for Islamic Finance to be considered as a suitable alternative to the existing Conventional system particularly during the crisis times. The study examined the financial performance of three Islamic banks in the Middle East alongside with other three conventional ones operating in the same region. The study used the Ratio Analysis technique for evaluating sample banks performance during the crisis times. The study suggested that although Islamic banks have shown some positive indicators, they were actually facing some difficulties which are seems to be relevant to integral parts of the system itself, and those drawbacks may need to be systematically handled before reaching any such conclusion. Keywords: Islamic Finance, Conventional Banks, Financial Performance, Challenges, Financial Crisis. JEL Classifications: E44, G01